Extrakorporale Stoßwellenlithotripsie - Klein, Jan-Thorsten; Netsch, Christopher; Sievert, Karl-Dietrich; Miernik, Arkadiusz; Westphal, Jens; Leyh, Herbert; Herrmann, Thomas Reinhard William; Olbert, Peter; Häcker, Axel; Bachmann, Alexander; Homberg, Roland; Schönthaler, Martin; et al. (Der Urologe, 2018)
Interventional treatment of stones essentially consists of three treatment modalities. Extracorporeal shockwave lithotripsy (ESWL), in addition to uterorenoscopy (URS) and percutaneous nephrolitholapaxy (PCNL) is an essential treatment pillar and is the only noninvasive therapy option for the treatment of urinary stones. After a long period of ESWL being the leading choice in stone treatment, the number of SWL interventions diminished in recent years in favor of the other two treatment modalities (URS and PCNL). This article describes the indications, surgical technique and management of complications of SWL.
"CME Zertifizierte Fortbildung"
Gesehen am 29.10.2019